Impact of Surgical Management of Endometrioma on Ovarian Reserve (Bangladesh Journal of Obstetrics & Gynaecology, 2022)
Objective: The aim of this study was to explore the outcome of surgical removal of endometriotic cyst on ovarian reserve.Materials and methods: This prospective observational study was carried out in Infertility Care and Research Centre, Dhaka, Bangladesh between January 2011 and December 2018. One hundred and fifty-five patients, who had an ultrasonographic diagnosis of endometrioma measuring ³3 cm and underwent surgical excision due to subfertility were the candidates for this study. The exclusion criteria were a) previous ovarian cystectomy, b) removal of one ovary, c) irregular menstrual cycle, d) polycystic ovarian syndrome e) endocrine disorder, f) low AMH (